Formal algebraic modelling of a city-wide smart parking system - Juan Roig, Pedro; Alcaraz, Salvador; Gilly, Katja; Filiposka, Sonja; Aknin, Noura (IEEE, 2020)
One of the main applications of smart cities are parking systems based on IoT/Fog technology. In this paper, we carry out the study of formal algebraic models for such systems. In that context, first of all we undertake the study of a model for a street with a single parking space, extending it with a string of parking spaces. Additionally, we add up some parking control at fog level in order to apply parking restrictions in case of local environment issues, such as air pollution or poor weather conditions. Eventually, we also add up an orchestration level so as to prevent parking related to intelligence information, such as traffic congestion down the road, an accident nearby, or adverse weather forecast to come.
Keywords: ACP, fog computing, IoT, formal protocol specification, networking